Physical-Chemical Processes at Mo-Doped Ceria-Yttria Stabilized Zirconia (Ysz) Anodes in Solid Oxide Fuel Cells Using Syngas Derived by the Distribution of Relaxation Times Method - Diaz-Aburto, I (Elsevier Ltd, 2023)
The use of environment-friendly carbonaceous fuels (such as, biomass and synthetic fuels) to produce electricity using solid oxide fuel cells (SOFCs) has emerged as a promising alternative to the use of high-purity hydrogen, which remains as a difficult to produce and store gas. Much effort has been put in the development of SOFC anodes highly active and stable for the use of carbonaceous fuels, such as ceria-based materials, but only recently research has focused on the comprehensive analysis of the interfacial physical-chemical processes affecting their performance. This work presents an in-depth analysis of the interfacial processes occurring at a Mo-doped ceria-yttria stabilized zirconia (YSZ) cermet anode in a SOFC using humidified syngas as fuel. To this end, electrochemical impedance spectroscopy (EIS) data is generated and analysed by the distribution of relaxation times (DRT) method. In addition, gas chromatography analysis of the internal reforming products generated under open circuit voltage (OCV) conditions and post-mortem analysis of the electrode materials after polarization are discussed in support of the DRT results. It is observed that the presence of carbon monoxide (CO) in fuel, as compared to pure hydrogen, influences the anodic charge transfer processes not only due to promotion of the water-gas-shift reaction at the anode two-phase (fuel | electrode) and three-phase (fuel | electrode | electrolyte) interfaces, but also because of its direct electrooxidation at the anode three-phase interfaces. The electrooxidation of carbon monoxide presents a slightly higher activation energy than the electrooxidation of hydrogen (ca. 1.86 and 1.21 eV, respectively), which explains the slower kinetics of SOFCs when using syngas as fuel. Additionally, other oxidation processes of CO at the anode interfaces (such as, the Boudouard reaction) promote the formation of carbon deposits lacking ordered structure, which are more reactive than graphitic structures formed at Ni-YSZ anodes but still can negatively influence the electrochemical kinetics. © 2023 Elsevier Ltd